Prognostic significance of U2AF1 mutations in myelodysplastic syndromes: a meta-analysis. Issue 3 (October 2020) - Li, Bixia; Zou, Duobing; Yang, Shujun; Ouyang, Guifang; Mu, Qitian
Introduction: Although the effects of U2 small nuclear RNA auxiliary factor 1 gene ( U2AF1 ) mutations on the outcomes of patients with myelodysplastic syndromes (MDS) have previously been investigated, their prognostic significance remains controversial. We performed a meta-analysis to investigate the impact of U2AF1 mutations on MDS progression. Methods: Two reviewers independently extracted information such as hazard ratios (HRs) and 95% confidential intervals (CIs) for overall survival (OS) and leukemia-free survival (LFS) as well as the number of surviving patients each year after diagnosis from the included studies. Results: Thirteen studies with a total of 3038 patients were included. The summary odds ratio (OR) for U2AF1 mutations with an OS of 5 years was 0.37, the summary HR for U2AF1 mutations in OS was 1.60, and the summary OR for an OS of 5 years in patients with U2AF1 S34 and U2AF1 Q157 was 3.68. There were no significant differences in leukemia-free survival or hypomethylating therapy response between patients with and without U2AF1 mutations. Conclusion: U2AF1 mutations were associated with poor survival in MDS patients, and patients with U2AF1 Q157 had a worse OS than those with U2AF1 S34 . Our findings suggest that MDS patients with U2AF1 mutations could benefit more from hypomethylation therapy.